1975
DOI: 10.1111/j.1476-5381.1975.tb07360.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Brain Tryptophan Metabolism Following Hydrocortisone Administration to Rats and Gerbils

Abstract: 1 Liver tryptophan pyrrolase activity is low in the mongolian gerbil (Meriones unguiculatus) and is not induced by hydrocortisone (5 mg/kg). In contrast, there is measurable activity in the rat liver and this is induced by hydrocortisone. In vivo measurements confirmed the absence of induction in gerbils but suggested that they were able to metabolize tryptophan. However, no detectable pyrrolase activity was found in any other tissues either before or after hydrocortisone. 2 In agreement with previous observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

1975
1975
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 30 publications
1
18
2
Order By: Relevance
“…However, when they perfused for 6 h, adding hydrocortisone to the medium, they found few significant changes of pyrrolase activity in terms of either tryptophan removal from the medium or appearance of kynurenine, the product of pyrrolase activity. This is at variance with in vivo studies which have demonstrated that steroids and tryptophan produce significant alterations in the rate of expired 14C02 from DL-[ring 2-'4C]-tryptophan (Moran & Sourkes, 1963;Green, 1969;Green et al, 1975b;Young & Sourkes, 1975). Kim & Miller (1969) however were also unable to find a statistically significant increase in "4CO2 excretion using these techniques.…”
Section: Introductioncontrasting
confidence: 43%
See 2 more Smart Citations
“…However, when they perfused for 6 h, adding hydrocortisone to the medium, they found few significant changes of pyrrolase activity in terms of either tryptophan removal from the medium or appearance of kynurenine, the product of pyrrolase activity. This is at variance with in vivo studies which have demonstrated that steroids and tryptophan produce significant alterations in the rate of expired 14C02 from DL-[ring 2-'4C]-tryptophan (Moran & Sourkes, 1963;Green, 1969;Green et al, 1975b;Young & Sourkes, 1975). Kim & Miller (1969) however were also unable to find a statistically significant increase in "4CO2 excretion using these techniques.…”
Section: Introductioncontrasting
confidence: 43%
“…There is some error in these results deriving from plasma tryptophan trapped in the blood vessels of the liver. Extracellular space in the liver has been calculated at 22.2% (Woods, Eggleston & Krebs, 1970 (Green et al, 1975b;Young & Sourkes, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the relationship between HPA axis hormones and cytokines, glucocorticoids stimulate the tryptophan metabolism through the KYN pathway in the liver, directly resulting in decreased CNS concentrations of serotonin. 152 …”
Section: The Inflammatory Hypothesis Of Depressionmentioning
confidence: 99%
“…This in turn would presumably decrease brain tryptophan. Recent evidence suggests that variations in activity of this enzyme can alter brain tryptophan concentrations (Green, Sourkes & Young, 1975;Green, Woods, Knott & Curzon, 1975).…”
Section: Discussionmentioning
confidence: 99%